PENGARUH LEVERAGE DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 - 2019 - TIA NOVIRA SUCIPTO (JURNAL ILMIAH MAKSITEK, 2021)
This study aims to determine the extent of the influence of Leverage and Tax Planning on Earnings Management inAgricultural Companies registered on the Indonesia Stock Exchange (IDX) with an observation period of 2015-2019. Thisresearch is a quantitative research using secondary data. The data used in this study is data based on financial statementsobtain through the official website of the Indonesia Stock Exchange (IDX), namely: www.idx.co.id. There are 25 populationsof agricultural companies and 8 agricultural companies are take as samples with the sampling method using purposesampling and data collection using the documentation method. The data processing program uses the SPSS Version 26program. The analytical method used in this study is the classical assumption test and multiple linear regression. The resultsshowed that the leverage variable has a negative effect on earnings management while the tax planning variable was aneffect on earnings management when tested partially. However, simultaneously leverage and tax planning have no effect onearnings management.